Travel advice for the immunocompromised traveler: prophylaxis, vaccination, and other preventive measures - Patel RR; Liang SY; Koolwal P; Kuhlmann FM (Dove Medical Press, 2015)
Rupa R Patel,1 Stephen Y Liang,1 Pooja Koolwal,2 Frederick Matthew Kuhlmann1 1Division of Infectious Diseases, 2Division of Medical Education, Washington University School of Medicine, St Louis, MO, USA Abstract: Immunocompromised patients are traveling at increasing rates. Physicians caring for these complex patients must be knowledgeable in pretravel consultation and recognize when referral to an infectious disease specialist is warranted. This article outlines disease prevention associated with international travel for adults with human immunodeficiency virus, asplenia, solid organ and hematopoietic transplantation, and other immunosuppressed states. While rates of infection may not differ significantly between healthy and immunocompromised travelers, the latter are at greater risk for severe disease. A thorough assessment of these risks can ensure safe and healthy travel. The travel practitioners’ goal should be to provide comprehensive risk information and recommend appropriate vaccinations or prevention measures tailored to each patient’s condition. In some instances, live vaccines and prophylactic medications may be contraindicated. Keywords: immunocompromised, vaccines, travel, malaria, diarrhea